Justices of the Indiana Supreme Court - Gugin, Linda C.; St. Clair, James E. (Indiana Historical Society Press in cooperation with the Indiana Supreme Court, 2010)
Explores the lives of each of the 106 men and women who have been members of the Indiana Supreme Court.